China's community-based crisis management model for COVID-19: A zero-tolerance approach - Shangguan, Ziheng; Wang, Mark Yaolin (Frontiers in Public Health, 2022)
Background: China was the first country to adopt the zero-tolerance approach to deal with Covid-19 and successfully control it. Some scholars generally attribute China's success to the top-down political system. This explanation is too superficial to interpret the internal logic of China's anti-epidemic, which have created a prejudice against China. This article attempts to comprehensively interpret China's Zero-tolerance Approach from the perspective of community-based crisis management. Methods: This article mainly uses descriptive and qualitative methods for research. Based on the theories of community-based disaster management (CBDM) and crisis management (CM), this article provides a comprehensive interpretation of China's Zero-tolerance Approach from the perspective of community-based crisis management (CBCM), which includes definition of China’s community and CBCM, management elements and steps. Based on the process of CBCM, this article discusses its secondary hazards and applicability. Results: China's CBCM basically replicates Singapore's crisis management model for SARS. With the co-operation of the community, it achieved universal coverage of prevention, detection and control. Conclusion: In addition to relying on the extreme power of the government to realize China's CBCM model, the two major factors of a submissive society and collectivism have played an important role. In addition, China’s CBCM model will lead to secondary hazards, such as privacy violations, heavy workloads for medical staff, financial pressure on local governments, and unemployment of migrant workers. Overall, China's CBCM model is essentially an excessive anti-pandemic strategy.